Analysis of the Constitution Court Verdict Number 46/PUU-XIV/2016 about Morality Criminal - Ansori Ansori; Muhammad Fuad Zain (Yuridika, 2019)
Indonesian Family Loves Alliance sees that Penal Code in article 284, 285 and 295 related to adultery, rape and molestation (sacrilege or abuse) which is contrary to religious values and the morale of the Indonesian people deliver to sue the Constitutional Court through judicial review with results was rejected. Five judges with judicial restraint argue that the State must protect rights and freedoms, not vice versa, but four others with judicial activism argue that the State must protect the rights of citizens by referring to the living law with develops in society. With no expansion of the meaning of the article a quo then LGBT, adultery, rape and molestation cannot be convicted. This verdict has been troubling most of Indonesians who want a change in the legal system, considering the legislative process that began in 1963 until now did not come to fruition. So the People’s Consultative Assembly and the President as a positive legislator are required to immediately revise the laws and regulations in accordance with religious norms and common laws that develops in society to avoid the violence or vigilante action which actually harms the community itself.